"Schrems II": The return of the Privacy Shield. Issue 39 (November 2020) - Tracol, Xavier
Abstract: On 16 July 2020, the Grand Chamber of the European Court of Justice rendered its landmark judgment in Case C-311/18 Data Protection Commissioner v. Facebook Ireland Ltd and Maximillian Schrems (" Schrems II"). The Grand Chamber invalidated the Commission decision on the adequacy of the data protection provided by the EU-US Privacy Shield. It however considered that the decision of the Commission on standard contractual clauses ("SCCs") issued by the Commission for the transfer of personal data to processors established in third states was legally valid. The legal effects of the judgment should first be clarified. In addition, it has far-reaching implications for companies which transfer personal data from the EU to the US. The judgment of the Grand Chamber has also far-reaching implications for transfers of personal data from the EU to other third states. Last, it has far-reaching implications for the UK in the context of Brexit. © 2020 Published by Elsevier Ltd. All rights reserved.